On isometrically containing maps for nonexpansive maps on finite metric spaces - Pol, Elzbieta; Pol, Roman (Topology Proceedings, 2021)
In this paper, for each n, we construct a map $f : X → Y$ between compact zero-dimensional metric spaces which is isometrically containing for the class of nonexpansive surjections between at most n-element metric spaces of diameter $≤ 1$.